A Match Made in Heaven: Entrepreneurship Among Evangelical Immigrants in the UK - David Andrew Clark (Religions)
Evangelical immigrants from the Global South have a high degree of confidence in their own ability to start a business in the UK, and they report a significant amount of entrepreneurial engagement within their communities. This article explores how these Christians developed their skills and dispositions, how they are launching businesses in the UK, and—most importantly—how the action of God can be perceived through their experiences. The author constructs a metanarrative which begins in the Global South. Through their encounter with evangelical faith, women and men are developing the ‘spiritual capital’ that has historically been proven to foster entrepreneurship. In many instances, however, this potential for success lies latent in a societal context that hampers and threatens entrepreneurial enterprise. The story then shifts to the UK. When these evangelicals immigrate, many find success in business as they choose to put their spiritual capital to work. It is here argued that the actions of God can be discerned within this story. In the same way that God acted in Biblical times to raise the helpless and to bless exiles in a foreign land, so he seen by his people to be working today.